Pengaruh Pelaksanaan Keselamatan Dan Kesehatan Kerja Terhadap Kinerja Pegawai - Mestina Hapsyah Hapsyah; Harmon Harmon (Jurnal Riset Bisnis dan Investasi, 2015)
Occupational health and safety are one of the important things that must be considered by the company to create safe and healthy working environment, especially for organizations that have the potential hazard and a high level of accident risk that could have an impact on performance. PT Indonesia Power Unit Kamojang is a company engaged in Geothermal Power Plant (PLTP) and has implemented a safety and health. This research aims to determine the effect of occupational health and safety on employee performance at PT Indonesia Power Unit Kamojang. The method which is used in this research is a descriptive method with quantitative approach. Data analysis method which is used in this research are descriptive analysis, correlation analysis, and regression analysis. The sample in this research as much as 149 respondents. Occupational health and safety currently on good category, it can be seen from working conditions, safety training and communication, the creation of healthy working environment, employee needs services and health care services. Then, employee performance also currently on good category, it can be seen from the result of work, work behavior, and personal qualities. The conclusion of this research is there’s an effect of occupational health and safety implementation on employee performance amounted to 23,7%.